Rheological and mechanical properties of self-compacting concrete with the addition of nano-silica and microsilica - Sánchez, E.; Bernal, J.; Moragues, A.; León, N. (Revista ALCONPAT, 2016)
Self-compacting concrete is the result of the redesign of quality mixtures with the ability to ensure its correct placement in strongly assembled structures, where the vibration process is too complicated and where there is the risk of altering the position of the reinforcement bars. Along with the advantages of this concrete and due to the greater demand for high performance concrete, silica fume is used, and more recently, nanomaterials with nano-silica as well; mainly, nano-silica. The objective of this work is to obtain self-compacting concretes with nano-silica, silica fume and binary mixtures of both, which satisfy the demands for high mechanical resistance and durability, determining that the dosage with the best features contains: 2.5% of nano and 2.5% of silica fume. Keywords: Self-compacting; nano-silica; silica fume; rheology; mechanical properties